Journey to the Center of the Earth: Description of a new troglomorphic litter-bug species inhabiting lava tubes in the Canary Islands (Heteroptera: Dipsocoromorpha: Ceratocombidae) - Roca-Cusachs, Marcos; Kim, Junggon; García-Becerra, Rafael; Jung, Sunghoon (Zootaxa, 2019)
Lava tubes in the Canary Islands have shown to have a great amount of endemic biodiversity belonging to a wide, and sometimes unexpected, range of taxa. In this paper, the first cave-dwelling species of a troglomorphic Dipsocoromorpha, Ceratocombus stysi sp. nov. is described making this finding the first named species of Dipsocoromorpha from the Canary Islands. Morphological information including diagnosis and genitalia description of the new species, together with biological and ecological notes are given.